Social network sites: Can they enhance employee productivity in an organization? - Preshita Neha Tudu; Pramod Pathak (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Social Network Siteshas allowed people to communicate, share, collaborate and publish information. Over the past few years, the availability and usage social network sites has emerged substantially and has led to a shift in cultural, allowing people to connect and collaborate in ways that were not possible otherwise. To embrace social network sites seamlessly in the organizations can be a real challenge for human resource management professionals as it affects the productivity of employee in the workplace. This research paper discusses the impact of social media sites on employee productivity and examines positive and negative perceptions of social networking sites.
Keywords: 650; Social network sites; Employee productivity; Employee satisfaction